Photonic Materials

The insertion of (ZnSnGe) x Ga1-x N 2 layers in InGaN quantum wells addresses efficiency issues in InGaN LEDs by improving electron-hole overlap and confinement, resulting in enhanced light emission efficiency.

JP2025502321APending Publication Date: 2025-01-24OHIO STATE INNOVATION FOUND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024542170
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-13
Filing Date
2022-11-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing InGaN-based LED devices exhibit low efficiency for longer wavelengths due to charge separation and mismatched lattice strain, which deteriorates with increasing In content and QW width, particularly in green and longer wavelength emissions.

Method used

A quantum well structure is designed with (ZnSnGe) x Ga1-x N 2 layers inserted between InGaN layers to enhance electron-hole wave function overlap and confinement, using pulsed MOCVD growth to achieve high-quality thin films with controlled band offsets and compositions.

Benefits of technology

The design significantly improves the radiation efficiency of InGaN-based LEDs by optimizing electron and hole confinement, leading to enhanced light emission properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502321000001_ABST
    Figure 2025502321000001_ABST
Patent Text Reader

Abstract

Disclosed herein is a photonic material. The photonic material includes a first layer, a second layer, and a third layer, the second layer being disposed between and in contact with the first layer and the third layer such that the second layer is sandwiched between the first layer and the third layer. In some examples, the first layer is In y Ga 1-y N, where y is 0 to 0.8. In some examples, the second layer comprises (Zn a Sn b Ge c ) x Ga d N2, where x is greater than 0 to 1, and a, b, c, and d are each independently 0 to 1, with the proviso that at least one of a, b, or c is greater than 0. In some examples, the third layer comprises In z Ga 1-z It contains N, and in the formula, z is 0 to 0.8.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 299,294, filed January 13, 2022, which is incorporated by reference in its entirety.

[0002] Statement regarding government support This invention was made with Government support under Grant / Contract No. DE-EE0008718 awarded by the U.S. Department of Energy. The Government has certain rights in this invention. [Background technology]

[0003] Extensive research has resulted in near 100% external quantum efficiency (EQE) for InGaN-based blue light emitting diodes (LEDs), but the efficiency of InGaN-based light emitters at longer visible wavelengths remains relatively low. The compositions, methods, and systems discussed herein address these and other needs. Summary of the Invention

[0004] In accordance with the purpose of the disclosed compositions, methods, and systems, as embodied and broadly described herein, the disclosed subject matter relates to photonic materials and methods of use thereof.

[0005] For example, highly efficient LED designs using quantum well engineering are disclosed herein.

[0006] Disclosed herein is a photonic material. The photonic material includes a first layer, a second layer, and a third layer, the second layer being disposed between and in contact with the first layer and the third layer such that the second layer is sandwiched between the first layer and the third layer. In some examples, the first layer is In y Ga 1-y N, where y is 0 to 0.8. In some examples, the second layer comprises (Zn aSn b Ge c ) x Ga d N2, where x is greater than 0 to 1, and a, b, c, and d are each independently 0 to 1, with the proviso that at least one of a, b, or c is greater than 0. In some examples, the third layer comprises In z Ga 1-z It contains N, and in the formula, z is 0 to 0.8.

[0007] In some examples, y and / or z are between 0.1 and 0.5, between 0.1 and 0.3, or y and / or z are 0.2.

[0008] In some examples, the first layer has a first average thickness between 0.1 nm and 5 nm. In some examples, the first layer has a first average thickness between 1 nm and 3 nm.

[0009] In some examples, the second layer has a second average thickness between 0.1 nm and 5 nm. In some examples, the second layer has a second average thickness between 0.5 nm and 0.7 nm.

[0010] In some examples, the second layer is (ZnSn) 0.5 Includes GaN2.

[0011] In some instances, d is equal to 1-x, so that the second layer is (Zn a Sn b Ge c ) x Ga 1-x Includes N2.

[0012] In some examples, the second layer is (ZnSn) 0.5 Ga 0.5 Includes N2.

[0013] In some examples, the third layer has a third average thickness of 0.1 nm to 5 nm. In some examples, the third layer has a third average thickness of 1 to 3 nm.

[0014] In some examples, the photonic material has an average composite thickness between 0.5 nm and 10 nm, the average composite thickness being the sum of the first average thickness, the second average thickness, and the third average thickness, hi some examples, the average composite thickness is between 1 nm and 5 nm, between 2.5 nm and 5 nm, or between 4 nm and 5 nm.

[0015] In some examples, the photonic material further includes a fourth layer disposed on the third layer such that the third layer is sandwiched between the second layer and the fourth layer, the fourth layer being comprised of Al w Ga 1-w N, where w is 0 to 1. In some examples, w is 0.1 to 0.5 or 0.1 to 0.3. In some examples, w is 0.2.

[0016] In some examples, the fourth layer has a fourth average thickness of 0.5 nm to 5 nm. In some examples, the fourth layer has a fourth average thickness of 0.5 nm to 4 nm, 1 nm to 2 nm, or 1.4 nm to 1.6 nm.

[0017] In some examples, the photonic material further includes a fifth layer disposed on the fourth layer such that the fourth layer is sandwiched between the fifth layer and the third layer, the fifth layer including GaN, In some examples, the fifth layer has a fifth average thickness of between 1 nm and 15 nm.

[0018] In some examples, the photonic material further includes a sixth layer disposed on the first layer such that the first layer is sandwiched between the sixth layer and the second layer, the sixth layer including GaN, In some examples, the sixth layer has a sixth average thickness of 1 nm to 15 nm.

[0019] In some examples, the photonic material has an electron wavefunction with a first confined state and a hole wavefunction with a first confined state, and an overlap of the electron wavefunction and the hole wavefunction in the first confined state in the photonic material is 1% or more, 5% or more, 15% or more, or 20% or more.

[0020] In some examples, the photonic material has a spontaneous emission spectrum with a peak wavelength of 500 nm or more, 550 nm or more, 600 nm or more, 650 nm or more, 700 nm or more, 1000 nm or more, or 1200 nm or more. In some examples, the photonic material has a spontaneous emission spectrum with a peak wavelength between 580 nm and 600 nm.

[0021] In some instances, the photonic material exhibits strong hole confinement in the second layer.

[0022] In some instances, the photonic material is 18 cm -3 ~5×10 18 cm -3 With a carrier concentration of 1×10 25 s -1 cm -3 It has a spontaneous radiative recombination rate per unit volume of equal to or greater than 100 nm.

[0023] In some instances, the spontaneous emission spectrum of the photonic material exhibits a peak wavelength of 500 nm or greater, and the peak wavelength is greater than 1×10 18 cm -3 ~5×10 18 cm -3 With a carrier concentration of 1×10 25 s -1 cm -3 eV -1 It has a strength of more than 10 ...

[0024] In some examples, the phonic material includes a quantum well structure.

[0025] Also disclosed herein is a light emitting diode (LED) that includes a quantum well structure that includes any of the photonic materials disclosed herein.

[0026] Also disclosed herein are methods of using any of the photonic materials disclosed herein, including using the photonic materials in semiconductor lasers, photovoltaic devices, solar cells, photodetectors, and the like.

[0027] Also disclosed herein are methods of making any of the photonic materials disclosed herein. In some examples, the methods can include MOCVD, such as pulsed MOCVD.

[0028] Additional advantages of the disclosed system and method will be set forth in part in the description that follows, and in part will be apparent from the description. The advantages of the disclosed system and method will be realized and attained by means of the elements and combinations particularly pointed out in the appended claims. It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosed system and method as claimed.

[0029] The details of one or more embodiments of the invention are set forth in the accompanying drawings and the description below. Other features, objects, and advantages of the invention will be apparent from the description and drawings, and from the claims.

[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects of the present disclosure and, together with the description, serve to explain the principles of the disclosure. [Brief description of the drawings]

[0031] [Figure 1] Schematic diagram of an InyGa1-yN / (ZnnaSnbGec)xGa1-xN2 / InzGa1-zN quantum well (QW) with the width of the QW (LQW), the position of the ZnSnGeGaN layer (z), and the thickness of the ZnSnGeGaN layer (L). The barriers surrounding the QW can be GaN and / or AlwGa1-wN / GaN. [Diagram 2] Schematic of precursor flow rates in each cycle of pulsed-mode MOCVD growth of ZnSn(Ga)N2. [Diagram 3] (f) AFM image (2 μm × 2 μm) of ZnSn(Ga)N2 film grown with TMSn pulse time of 15 s-ON and 45 s-OFF (sample H). [Figure 4A] Cross-sectional TEM image of sample H. The interface is indicated by the white dashed line. [Figure 4B] Atomic percentages plotted based on TEM_EDX results for sample H. [Diagram 5] Experimentally measured band alignment at the (ZnSn)0.5Ga0.5N2 / GaN interface. [Figure 6] Lattice constant versus energy gap for various III-N, Zn-IV-N, and Mg-IV-N compositions. [Figure 7] 1 is an energy band graph of an exemplary quantum well having a peak emission at 600 nm. [Figure 8] III-N and II-IV-N2 dual chamber MOCVD setup. [Figure 9] III-N and II-IV-N2 dual chamber MOCVD setup. [Figure 10] Single crystal ZnGeN2 grown on GaN via MOCVD. [Figure 11] Single crystal (ZnGe)0.94Ga0.12N2 grown on GaN via MOCVD. [Figure 12] Single crystal ZnSnN2 grown on GaN via MOCVD. [Figure 13] Single crystal ZnSnN2 grown on GaN via MOCVD. [Figure 14] Single crystal ZnSnN2 grown on GaN via MOCVD. [Figure 15] II-IV-Band offset between N2 and GaN. [Figure 16] Cross-sectional STEM image of a conventional InGaN QW. [Figure 17] Cross-sectional STEM image of an InGaN / ZnGeN2 / InGaN heterostructure QW. [Figure 18] Emission wavelength of IGN / ZGN QW. [Figure 19] Band gap alignment (showing conduction and valence band offsets) of InN, In0.2Ga0.8N, ZnSnN2, and ZnSnGa2N4 (e.g., (ZnSn)0.5GaN2) to GaN. [Figure 20] Schematic diagram of the proposed InGaN / ZnSnGa2N4 / AlGaN quantum wells with the quantum well width (LQW), the ZTGN layer position (Z), and the ZTGN layer thickness (L). [Figure 21A] Band alignment and electron and hole wave functions for the first confined energy state in a conventional GaN / 4 nm In0.25Ga0.75N / GaN QW designed for 590 nm peak spontaneous emission wavelength. [Figure 21B] Band alignment and electron and hole wave functions for the first confined energy state in a GaN / 2nm In0.2Ga0.8N / 0.6nm ZnSnGa2N4 / 2nm In0.2Ga0.8N / 1.5nm Al0.2Ga0.8N / GaN QW designed for 590nm peak spontaneous emission wavelength. [Figure 22A] Spontaneous emission spectra of conventional GaN / 4nm In0.25Ga0.75N / GaN (dashed line) QWs and GaN / 2nm In0.2Ga0.8N / 0.6nm ZnSnGa2N4 / 2nm In0.2Ga0.8N / 1.5nm Al0.2Ga0.8N / GaN (solid line) QWs for carrier concentrations of 1-5×1018cm-3. Both QWs were designed with a peak emission wavelength of 590 nm at a carrier concentration of 1×1018cm-3. [Figure 22B] Spontaneous light emission radiative recombination velocity of conventional GaN / 4nm In0.25Ga0.75N / GaN (dashed line) QWs and GaN / 2nm In0.2Ga0.8N / 0.6nm ZnSnGa2N4 / 2nm In0.2Ga0.8N / 1.5nm Al0.2Ga0.8N / GaN (solid line) QWs for carrier concentrations of 1-5×1018cm-3. Both QWs were designed with a peak emission wavelength of 590 nm at a carrier concentration of 1×1018cm-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The compositions, methods, and systems described herein may be more readily understood by reference to the following detailed description of certain aspects of the disclosed subject matter and examples included therein.

[0033] Before the present compositions, methods, and systems are disclosed and described, it is to be understood that the embodiments described below are not limited to specific synthetic methods or to particular reagents, as such may, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting.

[0034] Also, various publications are referenced throughout this specification. The disclosures of these publications in their entireties are incorporated by reference into this application in order to more fully describe the state of the art to which the disclosed subject matter pertains. The references disclosed are also discussed in the sentence in which the reference is cited and are individually and specifically incorporated by reference herein for the material contained therein.

[0035] General definition In this specification and the claims that follow, reference will be made to a number of terms that are defined to have the following meanings.

[0036] Throughout the description and claims of this specification, the term "comprise" and other forms of this term, such as "comprising" and "comprises," are intended to mean, but are not limited to, the inclusion of other additives, components, ingredients, or steps, for example, and are not intended to exclude.

[0037] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a composition" includes mixtures of two or more such compositions, reference to "an agent" includes mixtures of two or more such agents, reference to "the component" includes mixtures of two or more such components, and so forth.

[0038] "Optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and the description includes instances in which the event or circumstance occurs and instances in which it does not occur.

[0039] As used herein, ranges may be expressed as from "about" one particular value and / or to "about" another particular value. "About" means within 5% of the value, for example, within 4, 3, 2, or 1% of the value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, it is understood that the particular value forms another embodiment by using the antecedent "about." It will be further understood that the endpoints of each of the ranges are significant both in relationship to the other endpoint, and independently of the other endpoint.

[0040] Values ​​may be expressed herein as "average" values. "Average" generally refers to a statistical average value.

[0041] By "substantially" is meant within 5%, for example within 4%, 3%, 2%, or 1%.

[0042] "Exemplary" means "one example" and is not intended to convey an indication of a preferred or ideal embodiment. "Etc." is used in a limiting sense but rather for descriptive purposes.

[0043] Throughout this specification, the designators "first" and "second" are believed to be used solely to aid in distinguishing between various components and steps of the disclosed subject matter. The designators "first" and "second" are not intended to imply any particular order, quantity, priority, or importance to the components or steps modified by these terms.

[0044] References in this specification and in the concluding claims to parts by weight of a particular element or component in a composition indicate the weight relationship between the element or component and any other elements or ingredients in the composition or article for which the parts by weight are expressed. Thus, in a compound containing 2 parts by weight of component X and 5 parts by weight of component Y, X and Y are present in a weight ratio of 2:5, and are present in such ratio regardless of whether additional components are contained in the compound.

[0045] Weight percentages (wt %) of components are based on the total weight of the formulation or composition in which the component is included, unless otherwise specified.

[0046] As used herein, the term "or combinations thereof" refers to all permutations and combinations of the items listed before the term. For example, "A, B, C, or combinations thereof" is intended to include at least one of A, B, C, AB, AC, BC, or ABC, or, if order is important in the particular context, BA, CA, CB, CBA, BCA, ACB, BAC, or CAB. Following this example, combinations including one or more repeats of an item or term, such as BB, AAA, AB, BBC, AAABCCCC, CBBAAA, CABABB, etc., are expressly included. Those skilled in the art will understand that there is typically no limitation on the number of items or terms in any combination unless otherwise clear from the context.

[0047] Photonic materials and methods for making and using same Disclosed herein is a photonic material that includes a first layer, a second layer, and a third layer, the second layer being disposed between and in contact with the first layer and the third layer such that the second layer is sandwiched between the first layer and the third layer.

[0048] The first layer is In y Ga 1-yN, in the formula, y is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more , 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, or 0.75 or more). In some examples, y can be 0.8 or less (e.g., 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less, 0.25 or less, 0.24 or less, 0.23 or less, 0.22 or less, 0.21 or less, 0.20 or less, 0.19 or less, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of y can range from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, y can be 0 to 0.8 (e.g., 0 to 0.4, 0.4 to 0.8, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.5, 0 to 0.3, 0 to 0.1, 0.1 to 0.8, 0.2 to 0.8, 0.3 to 0.8, 0.5 to 0.8, 0.6 to 0.8, 0.7 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, y is 0.2. In some examples, the first layer is In y Ga 1-y It consists of N.

[0049] The first layer can have a first average thickness of 0.1 nanometers (nm) or more (e.g., 0.2 nm or more, 0.3 nm or more, 0.4 nm or more, 0.5 nm or more, 0.6 nm or more, 0.7 nm or more, 0.8 nm or more, 0.9 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, 2.4 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, or 4 nm or more). In some examples, the first layer can have a first average thickness of 5 nm or less (e.g., 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2.4 nm or less, 2.3 nm or less, 2.2 nm or less, 2.1 nm or less, 2.0 nm or less, 1.9 nm or less, 1.8 nm or less, 1.7 nm or less, 1.6 nm or less, 1.5 nm or less, 1.4 nm or less, 1.3 nm or less, 1.2 nm or less, 1.1 nm or less, 1.0 nm or less, 0.9 nm or less, 0.8 nm or less, 0.7 nm or less, 0.6 nm or less, 0.5 nm or less, 0.4 nm or less, 0.3 nm or less, or 0.2 nm or less). The first average thickness can range from any of the minimum values ​​above to any of the maximum values ​​above. For example, the first layer can have a first average thickness of 0.1 nm to 5 nm (e.g., 0.1 nm to 2.5 nm, 2.5 nm to 5 nm, 0.1 nm to 1 nm, 1 nm to 2 nm, 2 nm to 3 nm, 3 nm to 4 nm, 4 nm to 5 nm, 0.1 nm to 4 nm, 0.1 nm to 3 nm, 0.1 nm to 2 nm, 0.5 nm to 5 nm, 1 nm to 5 nm, 2 nm to 5 nm, 3 nm to 5 nm, 0.5 nm to 4.5 nm, 1 nm to 4 nm, or 1 to 3 nm). The average thickness can be measured using methods known in the art, such as evaluation by electron microscopy (e.g., cross-sectional TEM imaging).

[0050] The second layer is (Zn a Sn b Ge c ) x Ga dN2, wherein x is greater than 0 to 1, and a, b, c, and d are each independently 0 to 1, with the proviso that at least one of a, b, or c is greater than 0.

[0051] For example, x may be greater than 0 (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more). In some examples, x is 1 or less (e.g., 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less). 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of x can range from any of the minimum values ​​recited above to any of the maximum values ​​recited above. For example, x can be greater than 0 to 1 (e.g., greater than 0 to 0.5, 0.5 to 1, greater than 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0.8 to 1, greater than 0 to 0.9, greater than 0 to 0.8, greater than 0 to 0.7, greater than 0 to 0.6, greater than 0 to 0.4, greater than 0 to 0.3, greater than 0 to 0.1, 0.1 to 1, 0.2 to 1, 0.3 to 1, 0.5 to 1, 0.6 to 1, 0.7 to 1, 0.9 to 1, 0.1 to 0.9, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, x is 0.5. In some examples, x is 1.

[0052] In some examples, a is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more). In some examples, a is 1 or less (e.g., 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less). 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of a can range from any of the minimum values ​​recited above to any of the maximum values ​​recited above. For example, a can be 0 to 1 (e.g., 0 to 0.5, 0.5 to 1, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0.8 to 1, 0 to 0.9, 0 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.4, 0 to 0.3, 0 to 0.1, 0.1 to 1, 0.2 to 1, 0.3 to 1, 0.5 to 1, 0.6 to 1, 0.7 to 1, 0.9 to 1, 0.1 to 0.9, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, a is 0. In some examples, a is 1.

[0053] In some examples, b is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more). In some examples, b is 1 or less (e.g., 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less). 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of b can range from any of the minimum values ​​recited above to any of the maximum values ​​recited above. For example, b can be 0 to 1 (e.g., 0 to 0.5, 0.5 to 1, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0.8 to 1, 0 to 0.9, 0 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.4, 0 to 0.3, 0 to 0.1, 0.1 to 1, 0.2 to 1, 0.3 to 1, 0.5 to 1, 0.6 to 1, 0.7 to 1, 0.9 to 1, 0.1 to 0.9, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, b is 0. In some examples, b is 1.

[0054] In some examples, c is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more). In some examples, c is 1 or less (e.g., 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less). 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of c can range from any of the minimum values ​​recited above to any of the maximum values ​​recited above. For example, c can be 0 to 1 (e.g., 0 to 0.5, 0.5 to 1, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0.8 to 1, 0 to 0.9, 0 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.4, 0 to 0.3, 0 to 0.1, 0.1 to 1, 0.2 to 1, 0.3 to 1, 0.5 to 1, 0.6 to 1, 0.7 to 1, 0.9 to 1, 0.1 to 0.9, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, c is 0. In some examples, c is 1.

[0055] In some examples, d is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more). In some examples, d is 1 or less (e.g., 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of d can range from any of the minimum values ​​recited above to any of the maximum values ​​recited above. For example, d can be 0 to 1 (e.g., 0 to 0.5, 0.5 to 1, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0.8 to 1, 0 to 0.9, 0 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.4, 0 to 0.3, 0 to 0.1, 0.1 to 1, 0.2 to 1, 0.3 to 1, 0.5 to 1, 0.6 to 1, 0.7 to 1, 0.9 to 1, 0.1 to 0.9, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, d is 0. In some examples, d is 0.5. In some examples, d is 1.

[0056] In some instances, d is equal to 1-x, so that the second layer is (Zn a Sn b Ge c ) x Ga 1-x Includes N2.

[0057] In some examples, the second layer is (ZnSn) 0.5 Ga 0.5 In some examples, the second layer comprises (ZnSn) 0.5 Ga 0.5 It consists of N2.

[0058] In some examples, the second layer is (ZnSn) 0.5 In some examples, the second layer comprises GaN2. 0.5 It is made of GaN2.

[0059] The second layer can have a second average thickness of 0.1 nanometers (nm) or more (e.g., 0.2 nm or more, 0.3 nm or more, 0.4 nm or more, 0.5 nm or more, 0.6 nm or more, 0.7 nm or more, 0.8 nm or more, 0.9 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, 2.4 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, or 4 nm or more). In some examples, the second layer can have a second average thickness of 5 nm or less (e.g., 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2.4 nm or less, 2.3 nm or less, 2.2 nm or less, 2.1 nm or less, 2.0 nm or less, 1.9 nm or less, 1.8 nm or less, 1.7 nm or less, 1.6 nm or less, 1.5 nm or less, 1.4 nm or less, 1.3 nm or less, 1.2 nm or less, 1.1 nm or less, 1.0 nm or less, 0.9 nm or less, 0.8 nm or less, 0.7 nm or less, 0.6 nm or less, 0.5 nm or less, 0.4 nm or less, 0.3 nm or less, or 0.2 nm or less). The second average thickness can range from any of the minimum values ​​above to any of the maximum values ​​above. For example, the second layer can have a second average thickness of 0.1 nm to 5 nm (e.g., 0.1 nm to 2.5 nm, 2.5 nm to 5 nm, 0.1 nm to 1 nm, 1 nm to 2 nm, 2 nm to 3 nm, 3 nm to 4 nm, 4 nm to 5 nm, 0.1 nm to 4 nm, 0.1 nm to 3 nm, 0.1 nm to 2 nm, 0.5 nm to 5 nm, 1 nm to 5 nm, 2 nm to 5 nm, 3 nm to 5 nm, 0.2 nm to 4.5 nm, 0.3 nm to 4 nm, or 0.5 nm to 0.7 nm). The average thickness can be measured using methods known in the art, such as evaluation by electron microscopy (e.g., cross-sectional TEM imaging).

[0060] The third layer is In z Ga 1-zN, wherein z is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more). , 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, or 0.75 or more). In some examples, z can be 0.8 or less (e.g., 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less, 0.25 or less, 0.24 or less, 0.23 or less, 0.22 or less, 0.21 or less, 0.20 or less, 0.19 or less, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of z can range from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, z can be 0 to 0.8 (e.g., 0 to 0.4, 0.4 to 0.8, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.5, 0 to 0.3, 0 to 0.1, 0.1 to 0.8, 0.2 to 0.8, 0.3 to 0.8, 0.5 to 0.8, 0.6 to 0.8, 0.7 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, z is 0.2. In some examples, the third layer is In z Ga 1-z It consists of N.

[0061] The third layer can have a third average thickness of 0.1 nanometers (nm) or more (e.g., 0.2 nm or more, 0.3 nm or more, 0.4 nm or more, 0.5 nm or more, 0.6 nm or more, 0.7 nm or more, 0.8 nm or more, 0.9 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, 2.4 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, or 4 nm or more). In some examples, the third layer can have a third average thickness of 5 nm or less (e.g., 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2.4 nm or less, 2.3 nm or less, 2.2 nm or less, 2.1 nm or less, 2.0 nm or less, 1.9 nm or less, 1.8 nm or less, 1.7 nm or less, 1.6 nm or less, 1.5 nm or less, 1.4 nm or less, 1.3 nm or less, 1.2 nm or less, 1.1 nm or less, 1.0 nm or less, 0.9 nm or less, 0.8 nm or less, 0.7 nm or less, 0.6 nm or less, 0.5 nm or less, 0.4 nm or less, 0.3 nm or less, or 0.2 nm or less). The third average thickness can range from any of the minimum values ​​above to any of the maximum values ​​above. For example, the third layer can have a first average thickness of 0.1 nm to 5 nm (e.g., 0.1 nm to 2.5 nm, 2.5 nm to 5 nm, 0.1 nm to 1 nm, 1 nm to 2 nm, 2 nm to 3 nm, 3 nm to 4 nm, 4 nm to 5 nm, 0.1 nm to 4 nm, 0.1 nm to 3 nm, 0.1 nm to 2 nm, 0.5 nm to 5 nm, 1 nm to 5 nm, 2 nm to 5 nm, 3 nm to 5 nm, 0.5 nm to 4.5 nm, 1 nm to 4 nm, or 1 to 3 nm). The average thickness can be measured using methods known in the art, such as evaluation by electron microscopy (e.g., cross-sectional TEM imaging).

[0062] The photonic material can have, for example, an average composite thickness, where the average composite thickness is the sum of the first average thickness, the second average thickness, and the third average thickness. The average composite thickness can be, for example, 0.5 nm or more (e.g., 0.6 nm or more, 0.7 nm or more, 0.8 nm or more, 0.9 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, 2.4 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, 4 nm or more, 4.5 nm or more, 5 nm or more, 5.5 nm or more, 6 nm or more, 6.5 nm or more, 7 nm or more, 7.5 nm or more, 8 nm or more, 8.5 nm or more, 9 nm or more, or 9.5 nm or more). In some examples, the average composite thickness can be 10 nm or less (e.g., 9.5 nm or less, 9 nm or less, 8.5 nm or less, 8 nm or less, 7.5 nm or less, 7 nm or less, 6.5 nm or less, 6 nm or less, 5.5 nm or less, 5 nm or less, 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2.4 nm or less, 2.3 nm or less, 2.2 nm or less, 2.1 nm or less, 2.0 nm or less, 1.9 nm or less, 1.8 nm or less, 1.7 nm or less, 1.6 nm or less, 1.5 nm or less, 1.4 nm or less, 1.3 nm or less, 1.2 nm or less, 1.1 nm or less, 1.0 nm or less, 0.9 nm or less, 0.8 nm or less, 0.7 nm or less, 0.6 nm or less, 0.5 nm or less, 0.4 nm or less, 0.3 nm or less, or 0.2 nm or less). The average composite thickness may range from any of the minimum values ​​listed above to any of the maximum values ​​listed above.For example, the photonic material may have an average composite thickness of 0.5 nm to 10 nm (e.g., 0.5 nm to 5 nm, 5 nm to 10 nm, 0.5 nm to 2 nm, 2 nm to 4 nm, 4 nm to 6 nm, 6 nm to 8 nm, 8 nm to 10 nm, 0.5 nm to 9 nm, 0.5 nm to 8 nm, 0.5 nm to 7 nm, 0.5 nm to 6 nm, 0.5 nm to 4 nm, 0.5 nm to 3 nm, 1 nm to 10 nm, 2 nm to 10 nm, 3 nm to 10 nm, 4 nm to 10 nm, 6 nm to 10 nm, 7 nm to 10 nm, 9 nm to 10 nm, 1 nm to 9 nm, 1 nm to 7 nm, 1 nm to 5 nm, 2.5 nm to 5 nm, or 4 nm to 5 nm). The average thickness may be measured using methods known in the art, such as evaluation by electron microscopy (e.g., cross-sectional TEM imaging).

[0063] In some examples, the photonic material may be sandwiched between two barrier layers to form a quantum well.

[0064] In some examples, the photonic material can further include a fourth layer, which can be disposed on the third layer such that the third layer is sandwiched between the second layer and the fourth layer. The fourth layer can be Al w Ga 1-wN, where w is 0 or more (e.g., 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.10 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, 0.30 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more). In some examples, w is 1 or less (e.g., 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less). 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, or 0.05 or less). The value of w can range from any of the minimum values ​​recited above to any of the maximum values ​​recited above. For example, w can be 0 to 1 (e.g., 0 to 0.5, 0.5 to 1, 0 to 0.2, 0.2 to 0.4, 0.4 to 0.6, 0.6 to 0.8, 0.8 to 1, 0 to 0.9, 0 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.4, 0 to 0.3, 0 to 0.1, 0.1 to 1, 0.2 to 1, 0.3 to 1, 0.5 to 1, 0.6 to 1, 0.7 to 1, 0.9 to 1, 0.1 to 0.9, 0.1 to 0.8, 0.1 to 0.7, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.4, or 0.1 to 0.3). In some examples, w is 0.2. In some examples, the fourth layer is Al w Ga 1-w It can consist of N.

[0065] The fourth layer can have a fourth average thickness of 0.5 nm or more (e.g., 0.6 nm or more, 0.7 nm or more, 0.8 nm or more, 0.9 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, 2.4 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, or 4 nm or more). In some examples, the fourth layer can have a fourth average thickness of 5 nm or less (e.g., 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2.4 nm or less, 2.3 nm or less, 2.2 nm or less, 2.1 nm or less, 2.0 nm or less, 1.9 nm or less, 1.8 nm or less, 1.7 nm or less, 1.6 nm or less, 1.5 nm or less, 1.4 nm or less, 1.3 nm or less, 1.2 nm or less, 1.1 nm or less, or 1.0 nm or less). The fourth average thickness can range from any of the minimum values ​​above to any of the maximum values ​​above. For example, the fourth layer can have a fourth average thickness of 0.5 nm to 5 nm (e.g., 0.5 nm to 2.5 nm, 2.5 nm to 5 nm, 0.5 nm to 1 nm, 1 nm to 2 nm, 2 nm to 3 nm, 3 nm to 4 nm, 4 nm to 5 nm, 0.5 nm to 4 nm, 0.5 nm to 3 nm, 0.5 nm to 2 nm, 1 nm to 5 nm, 2 nm to 5 nm, 3 nm to 5 nm, 4 nm to 5 nm, 1 nm to 4 nm, 1 nm to 3 nm, 1 nm to 2 nm, or 1.4 nm to 1.6 nm). The average thickness can be measured using methods known in the art, such as evaluation by electron microscopy (e.g., cross-sectional TEM imaging).

[0066] In some examples, the photonic material may further include a fifth layer, and the fifth layer may be disposed on the fourth layer such that the fourth layer is sandwiched between the fifth layer and the third layer. In some examples, the fifth layer includes GaN. In some examples, the fifth layer is made of GaN.

[0067] In some examples, the fifth layer has a fifth average thickness of 1 nm or more (e.g., 1.5 nm or more, 2 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, 4 nm or more, 4.5 nm or more, 5 nm or more, 6 nm or more, 7 nm or more, 8 nm or more, 9 nm or more, 10 nm or more, 11 nm or more, 12 nm or more, 13 nm or more, or 14 nm or more). In some examples, the fifth layer has a fifth average thickness of 15 nm or less (e.g., 14 nm or less, 13 nm or less, 12 nm or less, 11 nm or less, 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5 nm or less, 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2 nm or less, or 1.5 nm or less). The fifth average thickness can range from any of the minimum values ​​above to any of the maximum values ​​above. For example, the fifth layer may have a fifth average thickness of 1 nm to 15 nm (e.g., 1 nm to 7 nm, 7 nm to 15 nm, 1 nm to 5 nm, 5 nm to 10 nm, 10 nm to 15 nm, 1 nm to 14 nm, 1 nm to 13 nm, 1 nm to 12 nm, 1 nm to 11 nm, 1 nm to 10 nm, 1 nm to 9 nm, 1 nm to 8 nm, 1 nm to 6 nm, 1 nm to 4 nm, 1 nm to 3 nm, 1 nm to 2 nm, 2 nm to 15 nm, 3 nm to 15 nm, 4 nm to 15 nm, 5 nm to 15 nm, 6 nm to 15 nm, 8 nm to 15 nm, 9 nm to 15 nm, 11 nm to 15 nm, 12 nm to 15 nm, 13 nm to 15 nm, 14 nm to 15 nm, 2 nm to 14 nm, or 3 nm to 13 nm). The average thickness may be measured using methods known in the art, such as evaluation by electron microscopy (eg, cross-sectional TEM imaging).

[0068] In some examples, the photonic material may further include a sixth layer, and the sixth layer may be disposed on the first layer such that the first layer is sandwiched between the sixth layer and the second layer. In some examples, the sixth layer includes GaN. In some examples, the sixth layer is made of GaN.

[0069] In some examples, the sixth layer has a sixth average thickness of 1 nm or more (e.g., 1.5 nm or more, 2 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, 4 nm or more, 4.5 nm or more, 5 nm or more, 6 nm or more, 7 nm or more, 8 nm or more, 9 nm or more, 10 nm or more, 11 nm or more, 12 nm or more, 13 nm or more, or 14 nm or more). In some examples, the sixth layer has a sixth average thickness of 15 nm or less (e.g., 14 nm or less, 13 nm or less, 12 nm or less, 11 nm or less, 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5 nm or less, 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2 nm or less, or 1.5 nm or less). The sixth average thickness can range from any of the minimum values ​​above to any of the maximum values ​​above. For example, the sixth layer may have a sixth average thickness of 1 nm to 15 nm (e.g., 1 nm to 7 nm, 7 nm to 15 nm, 1 nm to 5 nm, 5 nm to 10 nm, 10 nm to 15 nm, 1 nm to 14 nm, 1 nm to 13 nm, 1 nm to 12 nm, 1 nm to 11 nm, 1 nm to 10 nm, 1 nm to 9 nm, 1 nm to 8 nm, 1 nm to 6 nm, 1 nm to 4 nm, 1 nm to 3 nm, 1 nm to 2 nm, 2 nm to 15 nm, 3 nm to 15 nm, 4 nm to 15 nm, 5 nm to 15 nm, 6 nm to 15 nm, 8 nm to 15 nm, 9 nm to 15 nm, 11 nm to 15 nm, 12 nm to 15 nm, 13 nm to 15 nm, 14 nm to 15 nm, 2 nm to 14 nm, or 3 nm to 13 nm). The average thickness may be measured using methods known in the art, such as evaluation by electron microscopy (eg, cross-sectional TEM imaging).

[0070] The photonic materials described herein can have an electron wavefunction having a first confined state and a hole wavefunction having a first confined state, where the overlap of the electron wavefunction and the hole wavefunction at the first confined state in the photonic material is 1% or more (e.g., 2% or more, 3% or more, 4% or more, 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more). or more, 40% or more, 45% or more, 50% or more, 51% or more, 52% or more, 53% or more, 54% or more, 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more).

[0071] In some instances, the photonic material exhibits strong hole confinement in the second layer.

[0072] In some examples, the photonic material may have a wavelength of 500 nm or greater (e.g., 510 nm or greater, 520 nm or greater, 530 nm or greater, 540 nm or greater, 550 nm or greater, 560 nm or greater, 570 nm or greater, 580 nm or greater, 590 nm or greater, 600 nm or greater, 610 nm or greater, 620 nm or greater, 630 nm or greater, 640 nm or greater, 650 nm or greater, 660 nm or greater, 670 nm or greater, 680 nm or greater, 690 nm or greater, 700 nm or greater, 710 nm or greater, 720 nm or greater, 730 nm or greater, 740 nm or greater, 750 nm or greater, 760 nm or greater, 770 nm or greater, 780 nm or greater, 790 nm or greater, 780 nm or greater, 790 nm or greater, 790 nm or greater, 800 nm or greater, 810 nm or greater, 820 nm or greater, 830 nm or greater, 840 nm or greater, 850 nm or greater, 860 nm or greater, 870 nm or greater, 880 nm or greater, 8 ... and having a spontaneous emission spectrum with a peak wavelength of 1000 nm or more, 725 nm or more, 750 nm or more, 775 nm or more, 800 nm or more, 825 nm or more, 850 nm or more, 875 nm or more, 900 nm or more, 925 nm or more, 950 nm or more, 975 nm or more, 1000 nm or more, 1050 nm or more, 1100 nm or more, 1150 nm or more, 1200 nm or more, 1250 nm or more, or 1300 nm or more). In some examples, the photonic material has a wavelength of 1400 nm or less (e.g., 1350 nm or less, 1300 nm or less, 1250 nm or less, 1200 nm or less, 1150 nm or less, 1100 nm or less, 1050 nm or less, 1000 nm or less, 970 nm or less, 950 nm or less, 925 nm or less, 900 nm or less, 875 nm or less, 850 nm or less, 825 nm or less, 800 nm or less, 775 nm or less, 750 nm or less, The photonic material may have a spontaneous emission spectrum having a peak wavelength of 725 nm or less, 700 nm or less, 690 nm or less, 680 nm or less, 670 nm or less, 660 nm or less, 650 nm or less, 640 nm or less, 630 nm or less, 620 nm or less, 610 nm or less, 600 nm or less, 590 nm or less, 580 nm or less, 570 nm or less, 560 nm or less, 550 nm or less, 540 nm or less, or 530 nm or less. The peak wavelength of the spontaneous emission spectrum of the photonic material may range from any of the minimum values ​​recited above to any of the maximum values ​​recited above.For example, the photonic material may have a wavelength of 500 nm to 1400 nm (e.g., 500 nm to 950 nm, 950 nm to 1400 nm, 500 nm to 800 nm, 800 nm to 1100 nm, 1100 nm to 1400 nm, 500 nm to 1300 nm, 500 nm to 1200 nm, 500 nm to 1100 nm, 500 nm to 1000 nm, 500 nm to 900 nm, 500 nm to 700 nm, 500 nm to 600 nm, 550 nm to 1400 nm, 600 nm to 1400 nm, 700 nm to 1400 nm, 800 nm to 1400 nm, 900 nm to 1400 nm, The optical fiber may have a spontaneous emission spectrum having a peak wavelength of 500 nm to 700 nm, 500 nm to 570 nm, 525 nm to 535 nm, 570 nm to 590 nm, 580 nm to 600 nm, 590 nm to 620 nm, 595 to 605 nm, 620 nm to 750 nm, 680 nm to 690 nm, 750 nm to 1400 nm, 750 nm to 1000 nm, 1000 nm to 1400 nm, 800 nm to 1000 nm, or 500 nm to 1200 nm.

[0073] In some instances, the photonic material is 15 cm -3 or more (e.g., 5×10 15 cm -3 That's it, 1×10 16 cm -3 That's it, 5 x 10 16 cm -3 That's it, 1×10 17 cm -3 That's it, 5 x 10 17 cm -3 That's it, 1×10 18 cm -3 That's it, 2 x 10 18 cm -3 That's it, 3 x 10 18 cm -3 That's it, 4 x 10 18 cm -3 That's it, 5 x 10 18 cm -3 That's it, 6 x 10 18 cm -3 That's it, 7 x 10 18 cm-3 That's it, 8 x 10 18 cm -3 That's it, 9 x 10 18 cm -3 That's it, 1×10 19 cm -3 That's it, 5 x 10 19 cm -3 That's it, 1×10 20 cm -3 That's it, 5 x 10 20 cm -3 That's it, 1×10 21 cm -3 That's it, 5 x 10 21 cm -3 That's it, 1×10 22 cm -3 or more, or 5 x 10 22 cm -3 In some examples, the photonic material may have a carrier concentration of 1×10 23 cm -3 Less than (e.g., 5×10 22 cm -3 Below, 1×10 22 cm -3 Below, 5 x 10 21 cm -3 Below, 1×10 21 cm -3 Below, 5 x 10 20 cm -3 Below, 1×10 20 cm -3 Below, 5 x 10 19 cm -3 Below, 1×10 19 cm -3 Below, 9 x 10 18 cm -3 Below, 8 x 10 18 cm -3 Below, 7 x 10 18 cm -3 Below, 6 x 10 18 cm -3 Below, 5 x 10 18 cm -3 Below, 4×10 18 cm -3 Below, 3 x 10 18 cm -3 Below, 2 x 10 18 cm -3 Below, 1×1018 cm -3 Below, 5 x 10 17 cm -3 Below, 1×10 17 cm -3 or less, or 5 x 10 16 cm -3 The carrier concentration of the photonic material may range from any of the minimum values ​​listed above to any of the maximum values ​​listed above. For example, the photonic material may have a carrier concentration of 1×10 15 cm -3 ~1×10 23 cm -3 (For example, 1×10 15 cm -3 ~1×10 19 cm -3 , 1×10 19 cm -3 ~1×10 23 cm -3 , 1×10 15 cm -3 ~1×10 17 cm -3 , 1×10 17 cm -3 ~1×10 19 cm -3 , 1×10 19 cm -3 ~1×10 21 cm -3 , 1×10 21 cm -3 ~1×10 23 cm -3 , 1×10 15 cm -3 ~1×10 22 cm -3 , 1×10 15 cm -3 ~1×10 21 cm -3 , 1×10 15 cm -3 ~1×10 20 cm -3 , 1×10 15 cm -3 ~1×10 19 cm -3 , 1×10 15 cm -3 ~1×10 18cm -3 , 1×10 15 cm -3 ~1×10 17 cm -3 , 1×10 15 cm -3 ~1×10 16 cm -3 , 1×10 16 cm -3 ~1×10 23 cm -3 , 1×10 17 cm -3 ~1×10 23 cm -3 , 1×10 18 cm -3 ~1×10 23 cm -3 , 1×10 19 cm -3 ~1×10 23 cm -3 , 1×10 21 cm -3 ~1×10 23 cm -3 , 1×10 22 cm -3 ~1×10 23 cm -3 , 1×10 16 cm -3 ~1×10 22 cm -3 , 1×10 17 cm -3 ~1×10 21 cm -3 , 1×10 18 cm -3 ~1×10 20 cm -3 , 1×10 18 cm -3 ~1×10 19 cm -3 , or 1 × 10 18 cm -3 ~5×10 18 cm -3 ) carrier concentration.

[0074] In some instances, the photonic material is 18 cm -3 ~5×10 18 cm-3 (For example, 5×10 25 s -1 cm -3 That's it, 1×10 26 s -1 cm -3 That's it, 5 x 10 26 s -1 cm -3 That's it, 1×10 27 s -1 cm -3 That's it, 5 x 10 27 s -1 cm -3 That's it, 1×10 28 s -1 cm -3 That's it, 5 x 10 28 s -1 cm -3 That's it, 1×10 29 s -1 cm -3 or more, or 5 x 10 29 s -1 cm -3 (or more) with a carrier concentration of 1×10 25 s -1 cm -3 In some examples, the photonic material has a spontaneous radiative recombination rate per unit volume of 1×10 18 cm -3 ~5×10 18 cm -3 (For example, 5×10 29 s -1 cm -3 Below, 1×10 29 s -1 cm -3 Below, 5 x 10 28 s -1 cm -3 Below, 1×10 28 s -1 cm -3 Below, 5 x 10 27 s -1 cm -3 Below, 1×10 27 s -1 cm -3 Below, 5 x 10 26 s -1 cm -3 Below, 1×10 26 s -1cm -3 or less, or 5 x 10 25 s -1 cm -3 (or less) with a carrier concentration of 1×10 30 s -1 cm -3 The spontaneous radiative recombination rate per unit volume may be less than or equal to 1×10 18 cm -3 ~5×10 18 cm -3 The spontaneous radiative recombination rate per unit volume of the photonic material at a carrier concentration of 1×10 can range from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, the photonic material may have a carrier concentration of 1×10 18 cm -3 ~5×10 18 cm -3 (For example, 1×10 25 s -1 cm -3 ~1×10 27 s -1 cm -3 , 1×10 27 s -1 cm -3 ~1×10 30 s -1 cm -3 , 1×10 25 s -1 cm -3 ~1×10 26 s -1 cm -3 , 1×10 26 s -1 cm -3 ~1×10 27 s -1 cm -3 , 1×10 27 s -1 cm -3 ~1×10 28 s -1 cm -3 , 1×10 28 s -1 cm -3 ~1×10 29 s -1 cm -3 , 1×10 29 s -1 cm -3 ~1×1030 s -1 cm -3 , 1×10 25 s -1 cm -3 ~1×10 29 s -1 cm -3 , 1×10 25 s -1 cm -3 ~1×10 28 s -1 cm -3 , 1×10 26 s -1 cm -3 ~1×10 30 s -1 cm -3 , 1×10 28 s -1 cm -3 ~1×10 30 s -1 cm -3 , or 5 × 10 25 s -1 cm -3 ~5×10 29 s -1 cm -3 ) with a carrier concentration of 1×10 25 s -1 cm -3 ~1×10 30 s -1 cm -3 may have a spontaneous radiative recombination rate of

[0075] In some instances, the spontaneous emission spectrum of the photonic material exhibits a peak wavelength of 500 nm or greater, and the peak wavelength is greater than 1×10 18 cm -3 ~5×10 18 cm -3 (For example, 5×10 25 s -1 cm -3 eV -1 That's it, 1×10 26 s -1 cm -3 eV -1 That's it, 5 x 10 26 s -1 cm -3 eV -1 That's it, 1×1027 s -1 cm -3 eV -1 That's it, 5 x 10 27 s -1 cm -3 eV -1 That's it, 1×10 28 s -1 cm -3 eV -1 That's it, 5 x 10 28 s -1 cm -3 eV -1 That's it, 1×10 29 s -1 cm -3 eV -1 or more, or 5 x 10 29 s -1 cm -3 eV -1 (or more) with a carrier concentration of 1×10 25 s -1 cm -3 eV -1 In some examples, the spontaneous emission spectrum of the photonic material exhibits a peak wavelength greater than or equal to 500 nm, and the peak wavelength is greater than or equal to 1×10 18 cm -3 ~5×10 18 cm -3 (For example, 5×10 29 s -1 cm -3 eV -1 Below, 1×10 29 s -1 cm -3 eV -1 Below, 5 x 10 28 s -1 cm -3 eV -1 Below, 1×10 28 s -1 cm -3 eV -1 Below, 5 x 10 27 s -1 cm -3 eV -1 Below, 1×10 27 s -1 cm -3 eV -1 Below, 5 x 10 26 s -1 cm-3 eV -1 Below, 1×10 26 s -1 cm -3 eV -1 or less, or 5 x 10 25 s -1 cm -3 eV -1 (or less) with a carrier concentration of 1×10 30 s -1 cm -3 eV -1 It has a strength of 1×10 18 cm -3 ~5×10 18 cm -3 The intensity of the peak wavelength of the spontaneous emission spectrum of the photonic material at a carrier concentration of 1×10 can range from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, the spontaneous emission spectrum of the photonic material exhibits a peak wavelength of 500 nm or greater, and the peak wavelength is greater than or equal to 1×10 18 cm -3 ~5×10 18 cm -3 (For example, 1×10 25 s -1 cm -3 eV -1 ~1×10 27 s -1 cm -3 eV -1 , 1×10 27 s -1 cm -3 eV -1 ~1×10 30 s -1 cm -3 eV -1 , 1×10 25 s -1 cm -3 eV -1 ~1×10 26 s -1 cm -3 eV -1 , 1×10 26 s -1 cm -3 eV -1 ~1×10 27 s -1 cm -3 eV -1, 1×10 27 s -1 cm -3 eV -1 ~1×10 28 s -1 cm -3 eV -1 , 1×10 28 s -1 cm -3 eV -1 ~1×10 29 s -1 cm -3 eV -1 , 1×10 29 s -1 cm -3 eV -1 ~1×10 30 s -1 cm -3 eV -1 , 1×10 25 s -1 cm -3 eV -1 ~1×10 29 s -1 cm -3 eV -1 , 1×10 25 s -1 cm -3 eV -1 ~1×10 28 s -1 cm -3 eV -1 , 1×10 26 s -1 cm -3 eV -1 ~1×10 30 s -1 cm -3 eV -1 , 1×10 28 s -1 cm -3 eV -1 ~1×10 30 s -1 cm -3 eV -1 , 5×10 25 s -1 cm -3 eV -1 ~5×10 29 s -1 cm -3 eV -1 , or 5×1026 s -1 cm -3 eV -1 ~5×10 29 s -1 cm -3 eV -1 ) with a carrier concentration of 1×10 25 s -1 cm -3 eV -1 ~1×10 30 s -1 cm -3 eV -1 It has a strength of.

[0076] Also described herein are light emitting diodes (LEDs) that include quantum well structures, which may include any of the photonic materials described herein. Also described herein are semiconductor lasers, photovoltaic devices (solar cell devices), photodetectors, and the like that include any of the photonic materials described herein.

[0077] Also disclosed herein are methods for making the photonic materials described herein. For example, the methods may include depositing layers in the appropriate order, and the layers may be deposited by epitaxial growth techniques, such as metalorganic chemical vapor deposition (MOCVD) (such as pulsed MOCVD), molecular beam epitaxy (MBE), pulsed laser deposition (PLD), or combinations thereof. In some examples, the methods may include pulsed MOCVD.

[0078] Although several embodiments of the invention have been described, it should be understood that various modifications may be made without departing from the spirit and scope of the invention. Accordingly, other embodiments are within the scope of the following claims.

[0079] The following examples are intended to further illustrate certain aspects of the systems and methods described herein, and are not intended to limit the scope of the claims. EXAMPLES

[0080] The following examples are described below to illustrate the methods and results according to the disclosed subject matter. These examples are not intended to be inclusive of all aspects of the subject matter disclosed herein, but rather to illustrate representative methods and results. These examples are not intended to exclude equivalents and variations of the present invention, which will be apparent to those skilled in the art.

[0081] Efforts have been made to ensure accuracy with respect to numbers (e.g., amounts, temperature, etc.), but some errors and deviations should be accounted for. Unless otherwise indicated, parts are parts by weight, temperature is in °C or is at ambient temperature, and pressure is at or near atmospheric. There are many variations and combinations of measurement conditions, e.g., component concentrations, temperatures, pressures, and other measurement ranges and conditions that can be used to optimize the described processes.

[0082] Example 1 – Highly efficient LED design using quantum well engineering Extensive research and development over the past two decades has resulted in near 100% external quantum efficiency (EQE) for InGaN-based blue light-emitting devices (Damilano et al. J. Phys. D: Appl. Phys. 2015, 48, 40300), but the efficiency of devices emitting longer visible wavelengths remains relatively low. Spontaneous polarization originating from the lack of inversion symmetry of the wurtzite structure (Keller et al. Semicond. Sci. Technol. 2014, 29, 113001) and piezoelectric polarization caused by lattice mismatch-induced strain (Han et al. J. Appl. Phys. 2016, 120, 103102) lead to internal electric fields in different regions of the QWs and associated localization of electrons and holes in InGaN quantum well (QW)-based light-emitting devices (Damilano et al. J. Phys. D: Appl. Phys. 2015, 48, 403001). This problem worsens with increasing In content and QW width, inhibiting the efficiency of InGaN-based devices emitting in the green or longer wavelengths.

[0083] Attempts to date to address the efficiency issues of InGaN-based green and longer wavelength light emitting devices include nonpolar or semipolar InGaN (Han et al. J. Appl. Phys. 2016, 120, 103102), staggered InGaN QWs (Zhao et al. Opt. Express 2011, 19, A991), strain-compensated InGaN / AlGaN QWs (Zhao et al. IEEE J. Quantum Electron. 2009, 45, 66; Zhao et al. Opt. Quantum Electron. 2008, 40, 301), type-II InGaN / GaNAs QWs (Arif et al. Appl. Phys. Lett. 2008, 92, 011104), and InGaN-delta InN QWs (Zhao et al. al. Appl. Phys. Lett. 2010, 97, 131114) to minimize charge separation. Recently, Han et al. proposed a type-II InGaN / ZnGeN2 QW-based design for blue and green light-emitting diodes. In this design, a ZnGeN2 layer sandwiched between two InGaN layers prevents the overlap of electron and hole wave functions (Γ) due to hole confinement due to the large band offset with InGaN. e-h ) significantly improves the lattice constant (Han et al. J. Appl. Phys. 2016, 120, 103102).

[0084] Previously, Zhao et al. proposed a QW structure design based on InGaN / ZnSnN2 QW structure (US Pat. No. 11,355,668), aiming to improve the overlap of electron-hole wavefunctions and therefore enhance the radiation efficiency by inserting a thin layer of ZnSnN2 into the InGaN QW.

[0085] Here, (Zn a Sn b Ge c ) x Ga 1-x N2 is inserted into the InGaN QW. As shown in Figure 1, the total thickness of the QW is L QW (Zn a Sn b Gec ) x Ga 1-x The thickness of the N2 layer is L. (Zn a Sn b Ge c ) x Ga 1-x The position of the N2 layer is from the left side of the QW (z = 0) to the right side of the QW (z = L QW -L) can be adjusted. (Zn a Sn b Ge c ) x Ga 1-x N2 materials are II-IV-N2[Zn a Sn b Ge c The Ga composition 1-x can be adjusted from 0 to less than 1. In the special case of 1-x=0, the material is Zn a Sn b Ge c N2. When the group II (Zn) / group IV (Sn+Ge) atomic ratio a / (b+c)=1, the stoichiometric Zn(Sn b Ge 1-b )N2. The b / c ratio of group IV elements Sn and Ge can vary from 0:1 to 1:0. The In composition of the InGaN sublayers y and z can be different. a Sn b Ge c ) x Ga 1-x Band offset between N2: ΔE c , ΔE v varies with the alloy composition. To achieve good confinement of the hole wavefunction near the center of the QW in the valence band, the Ga composition should be kept below 70%. Due to the lighter effective mass of the electron in the conduction band, band structure engineering has a weaker effect on the electron wavefunction. High purity GaN can be used as a barrier on both sides of the QW. To improve the electron confinement in the conduction band, AlGaN layers with larger barrier heights can be implemented. The Al composition w can vary from 0 to 1, and the thickness of the AlGaN layer (L AlGaN ) is 0~L GaN can vary.

[0086] The design of the QW structure is based on the experimental results for MOCVD growth of ZnSn(Ga)N2. A pulsed MOCVD growth technique was implemented to achieve Sn-droplet-free ZnSnN2 thin films grown at high temperatures. DEZn, TMSn, TMGa, and ammonia were used as precursors for Zn, Sn, Ga, and N, respectively. The TMGa and NH3 molar flow rates were set to 90.63 μmol / min and 178 μmol / min, respectively. For ZnSn(Ga)N2 growth, the reactor pressure was set to 500 Torr, and the growth temperature was varied from 560 °C to 580 °C. The DEZn, TMSn, and NH3 molar flow rates were set to 36.58 μmol / min, 36.48 μmol / min, and 201 μmol / min, respectively.

[0087] For TMSn pulsed mode growth, the TMSn flow is designed to be periodic on and off while maintaining constant flow rates of DEZn and NH3. Figure 2 shows a schematic diagram of pulsed mode growth. The TMSn flow rate is changed by t for each pulse cycle while maintaining constant flow rates of DEZn and NH3. _ON (flow into the chamber) and t _OFF (Bypass). This pulse cycle was controlled by N c Repeated times.

[0088] FIG. 3 demonstrates high quality ZnSn(Ga)N2 film growth with good surface morphology and an RMS of 7.12 nm.

[0089] The cross-sectional TEM image of sample H is shown in FIG. 4A, revealing high crystal quality and stoichiometric Zn / Sn ratio. The white dashed line indicates the ZnSn(Ga)N2 / GaN interface, which shows a sharp interface with epitaxial relationship. From the TEM_EDX measurement, the grown film has stoichiometric Zn / Sn ratio and 50% GaN alloy, as plotted in FIG. 4B. A series of MOCVD growth studies demonstrate that pulsed mode MOCVD growth is feasible to achieve Sn droplet-free growth of ZnSn(Ga)N2 films. In-situ GaN re-grown layer and optimized TMSn pulse period can achieve high quality ZnSn(Ga)N2 film growth.

[0090] Using XPS measurements, 20 nm thick GaN samples, 20 nm thick (ZnSn) 0.5 Ga 0.5 N2 sample and 2 nm thick (ZnSn) 0.5 Ga 0.5 Three samples of N2 / GaN heterostructure samples were used to (ZnSn) 0.5 Ga 0.5 The valence band offset between N2 and GaN was determined. (ZnSn) 0.5 Ga 0.5 The core energy levels and VBM positions determined for the N2 sample are listed in Table 1. [Table 1]

[0091] The average of the valence band offsets determined using the Zn 3d band and the Sn 3d band was used to determine the VBM of GaN (ZnSn) 0.5 Ga 0.5 The valence band maximum of N2 is aligned. Therefore, (ZnSn) 0.5 Ga 0.5 The V between N2 and GaN was extracted to be 0.97±0.05 eV. (ZnSn) 0.5 Ga 0.5 The band alignment of N2 with GaN is shown in FIG. 5 using the average of the VBO values ​​determined using the Zn 3d and Sn 3d bands.

[0092] Example 2 - Highly efficient InGaN LEDs emitting green, amber and beyond Highly efficient LEDs with green, amber, and longer wavelengths using III-nitride / II-IV-nitride heterostructures as the active medium are described herein. MOCVD development of heterostructures consisting of low indium content InGaN and ZnGeN2 or ZnSnN2 is used to surpass the current technology based on phosphor-converted LEDs (Figures 6, 7). This approach leverages the increased flexibility of tailoring the active region of the quantum well to decrease the emission wavelength or increase the electron-hole wavefunction overlap, opening up new ways to extend the emission wavelength of InGaN quantum well LEDs without using high indium content InGaN and significantly improve the internal quantum efficiency.

[0093] Described herein are experiments designed to achieve highly efficient green, amber, and longer wavelength LEDs using III-N / II-IV-N2 heterostructures. This concept offers the opportunity to extend the emission wavelength of InGaN QWs using low In content by using closely lattice-matched materials and their large band offsets.

[0094] The MOCVD growth window of high crystal quality ZnGeN2 and ZnSnN2 is explored. (In)GaN-ZnGeN2 QW green LEDs with IQE >60% and InGaN-ZnSnN2 QW amber LEDs with IQE >50% (optical) are also explored. Electrically injected green LEDs with IQE >60% and amber LEDs with IQE >50% are explored.

[0095] A III-N and II-IV-N2 dual chamber MOCVD setup can be used (FIGS. 8, 9), which has five hydride gas channels and seven alkyl channels. The five hydride channels include SiH4 / He (regular), SiH4H2 (dual dilution), GeH4 / He (regular), Spare (space for future hydride sources on the panel), NH3 (one channel), and H2 (carrier gas, switchable to N2 carrier gas). The seven alkyl channels include TMAl (dual dilution), TMG1 (dual dilution), TEG1 (regular), TMI1 (regular), CP2MG1 (regular), DEZn (regular), and tetramethylstannane (CH4H 12 There are no other reports of the growth of II-IV-nitrides by MOCVD. Furthermore, there are no other dual chamber configurations that can support the growth of both II-IV-nitrides and III-nitrides.

[0096] The devices were grown by MOCVD of single-crystalline ZnGe(Ga)N2 on GaN and demonstrated high crystal quality with sharp interfaces (Figures 10-11) (Karim et al. J Phys. D: Appl. Phys. 2021, 54(24), 245102).

[0097] The devices demonstrated MOCVD growth of single crystal ZnSn(Ga)N 2 on GaN (FIGS. 12-14, 4A, and 4B).

[0098] Through XPS measurements, we determined a large band offset between II-IV-N2 / GaN (Figures 5 and 15). The band offset ΔE between ZnGeN2 / GaN c First experimental determination of =1.55 eV. (ZnSn) 0.5 Ga 0.5 N2 / GaN band offset ΔE c = 0.97 eV.

[0099] We have realized an InGaN / ZnGeN2 heterostructure QW. Cross-sectional STEM images of a conventional InGaN QW and an InGaN / ZnGeN2 / InGaN heterostructure QW are shown in Figures 16 and 17, respectively (Karim et al. ACS Crys. Growth Des. 2022, 22(1), 131-139).

[0100] The emission wavelength of the IGN / ZGN QWs is red-shifted compared to the conventional QWs, and the magnitude of the shift depends on the position of the ZnGeN2 layer (Figure 18).

[0101] Electrically injected InGaN / II-IV-N2 heterostructure QW LEDs are investigated. Electroluminescence wavelength tuning by optimizing the position or thickness of the II-IV-N2 layer is investigated.

[0102] Example 3 - Design of InGaN-ZnSnGa2N4 quantum wells for high efficiency amber light emitting diodes Abstract. A type-II InGaN-ZnSnGa2N4 quantum well (QW) structure is proposed and investigated as the active region for high-efficiency amber (λ ~ 590 nm) light-emitting diodes (LEDs), which are currently a major challenge in high-purity InGaN-based LEDs. 0.5 A GaN2) layer is inserted into the InGaN QW to improve the confinement of the hole wavefunction in the valence band, and an AlGaN layer is incorporated into the quantum barrier to help better confine the electron wavefunction in the conduction band. The band structure of the InGaN-ZnSnGa2N4 QW is numerically simulated based on the experimentally measured band offset between ZnSnGa2N4 and GaN. For the InGaN-ZnSnGa2N4 QW design, a low In content (20%) is needed in the InGaN layer to reach the peak emission wavelength of about 590 nm, whereas a 25% In composition is needed to reach the same emission wavelength for a conventional InGaN QW with the same layer thickness. Furthermore, the electron-hole wavefunction overlap (Γ) for the InGaN-ZnSnGa2N4 QW design is e1-hh1) reaches 18% for an emission wavelength of about 590 nm, a significant improvement from conventional InGaN QWs (5%) emitting at the same wavelength. The increased overlap of electron-hole wave functions leads to roughly a 14-fold enhancement in the spontaneous light emission radiative recombination rate of InGaN-ZnSnGa2N4QWs compared to conventional InGaN QWs with higher In composition. The InGaN-ZnSnGa2N4QW structural design may be promising to open up a new way to achieve highly efficient amber LEDs.

[0103] Introduction. In the past decades, significant efforts have been made to improve the performance of InGaN-based green, yellow, and amber light-emitting diodes (LEDs), especially the high efficiency LEDs already achieved by InGaN (blue) and III-V (red) material systems. Although InGaN-based LED efficiency has improved significantly (Lv et al. ACS Photonics 2019, 6, 130; Alhassan et al. Opt. Express 2016, 24, 17868; Jiang et al. Photonics Res. 2019, 7, 144; Marcinkevicius et al. Appl. Phys. Lett. 2021, 119, 071102), the efficiency of amber LEDs remains the lowest in the visible wavelength range (DOE BTO Solid-State Lighting Program, “2022 DOE SSL R&D Opportunities”). InGaN quantum well (QW) based light emitting diodes face one fundamental challenge caused by the large polarization induced electric field due to the asymmetric wurtzite crystal structure (spontaneous polarization) and strained QW (piezoelectric polarization). This leads to a separation of the electron and hole wave functions, reducing the radiative recombination rate of charge carriers (Bernardini et al. Phys. Rev. B 2001, 63, 193201). Due to the need for relatively higher In content and thicker QWs, InGaN QW LEDs with emission wavelengths beyond blue and green are more susceptible to the detrimental effects of internal electrostatic fields (Damilano et al. J. Phys. Appl. Phys. 2015, 48, 403001).

[0104] Traditionally, LED structures grown along nonpolar or semipolar directions such as the a-plane and m-plane (DOE BTO Solid-State Lighting Program, “2022 DOE SSL R&D Opportunities”; Schmidt et al. Jpn. J. Appl. Phys. 2007, 46, L190; Farrell et al. Jpn. J. Appl. Phys. 2007, 46, L761) were intended to eliminate or reduce the large polarization fields in InGaN QWs. Other approaches reported to overcome this challenge include staggered InGaN QWs (Zhao et al. IEEE J. Sel. Top. Quantum Electron. 2009, 15, 1104; Zhao et al. Opt. Express 2011, 19, A991; Park et al. Appl. Phys. Lett. 2009, 94, 041109; Arif et al. IEEE J. Quantum Electron. 2008, 44, 573), strain-compensated InGaN-AlGaN QWs (Zhao et al. IEEE J. Quantum Electron. 2009, 45, 66; Zhao et al. Opt. Quantum Electron. 2008, 40, 301), and type-II InGaN-GaAsN QWs (Arif et al. Appl. Phys. Lett. 2008, 92, 011104; Park et al. QW designs include InGaN-delta-InN QWs (Zhao et al. Appl. Phys. Lett. 2010, 97, 131114), InGaN-delta-InN QWs (Zhao et al. Appl. Phys. Lett. 2010, 97, 131114), and InGaN QWs with delta-AlGaN layers (Park et al. Appl. Phys. Lett. 2006, 88, 202107; Park et al. Appl. Phys. Lett. 2007, 90, 023508). Band structure engineering in these QWs results in a shift of the electron and hole wavefunctions, thus improving the electron-hole wavefunction overlap and radiative recombination velocity.Significant enhancement of the internal quantum efficiency (IQE) of InGaN QWs has also been reported recently by forming "V-pits" (Marcinkevicius et al. Appl. Phys. Lett. 2021, 119, 071102) at threading dislocations. In-rich clusters (Wu et al. Appl. Phys. Lett. 1998, 72, 692) can create potential barriers around dislocations and suppress non-radiative recombination (Hangleiter et al. Phys. Rev. Lett. 2005, 95, 127402). However, to achieve longer emission wavelengths, these QW designs still require high In composition or thick QWs, which results in limited radiative efficiency. In addition, rare-earth doped (Er, Eu)GaN has been investigated as an active region for green and red emission (Heikenfeld et al. Appl. Phys. Lett. 2000, 76, 1365; Morishima et al. Phys. Status Solidi A 1999, 176, 113; Fragkos et al. Sci. Rep. 2018, 8, 13365; Fragkos et al. Sci. Rep. 2017, 7, 1; Timmerman et al. Phys. Rev. Appl. 2020, 13, 014044).

[0105] Recently, it has been reported that the strategic insertion of a single ZnGeN2 or ZnSnN2 layer into InGaN QW, i.e., InGaN-ZnGeN2, InGaN-ZnSnN2 type-II QW structures, shows a significant improvement in the radiative efficiency in InGaN-based LEDs (Han et al. J. Appl. Phys. 2016, 120, 103102; Karim et al. J. Appl. Phys. 2018, 124, 034303). The successful insertion of a thin ZnGeN2 layer into InGaN QW has also been experimentally demonstrated (Karim et al. Cryst. Growth Des. 2021, 22, 131). Meanwhile, the large conduction band offset between InGaN and ZnGeN2 weakens the confinement of the electron wave function in the ZnGeN2 layer, which limits the radiative recombination of electrons and holes. ZnSnN2 features a more favorable alignment with GaN in both the valence and conduction bands (Punya et al. Phys.Rev.B 2013,88,075302; Jaroenjittichai et al. Phys.Rev.B 2017,96,079907), which maintains the strong confinement of the hole wavefunction in the valence band without sacrificing the confinement of the electron wavefunction in the conduction band. Thus, large electron-hole wavefunction overlap and high IQE can be achieved for LEDs with longer peak emission wavelengths (~600 nm) (Karim et al. J.Appl.Phys.2018,124,034303). However, due to the relatively low MOCVD growth temperature required for ZnSnN2, the insertion of a ZnSnN2 monolayer into an InGaN QW can be challenging. Recently, to address the formation of Sn droplets at higher growth temperatures of ZnSnN2, a pulsed-mode MOCVD growth method was implemented to achieve stoichiometric ZnSnGa2N4 alloys (Zhang et al. Cryst. Growth Des. 2022, 22, 5004). The experimentally determined band offset (ΔE V = 0.96 eV and ΔE C=0.18 eV) (Zhang et al. Cryst. Growth Des. 2022, 22, 5004) presents a promising type-II InGaN-ZnSnGa2N4 QW heterostructure with improved radiative efficiency at long emission wavelengths.

[0106] In this work, the design of a type-II InGaN-ZnSnGa2N4 QW structure for highly efficient amber LEDs using a self-consistent six-band k·p method is described (Zhao et al. IEEE J. Quantum Electron. 2009, 45, 66). Calculations of the band structure were performed taking into account the polarization field, strain effects, and carrier screening effects. Spontaneous photoluminescence radiative recombination rates were calculated for both InGaN-ZnSnGa2N4 QW and conventional InGaN QW emitting at about 590 nm, and the QW designs described herein are estimated to be as low as 1-5×10 18 cm -3 This shows an improvement of about 14 times in the carrier concentration range.

[0107] Concept and design details. In this design, a thin layer of ZnSnGa2N4 is inserted in the active region to act as a hole confinement layer. Strain-free GaN, InN, and In 0.2 Ga 0.8 The band alignment of ZnSnGa2N4 and ZnSnN2 with N is shown in Figure 19. The band offset between ZnSnGa2N4 and GaN was determined using XPS measurements (Zhang et al. Cryst. Growth Des. 2022, 22, 5004), while the band offset value between ZnSnN2 and GaN is from first-principles calculations (Punya et al. Phys. Rev. B 2013, 88, 075302; Jaroenjittichai et al. Phys. Rev. B 2017, 96, 079907). The unique band alignment leads to strong hole confinement in the ZnSnGa2N4 layer. A schematic diagram of the proposed design is shown in Figure 20. The thin AlGaN layer can better confine the electron wavefunction in the QW active region. The peak emission wavelength (λ) of the conventional InGaN (IGN) QW is 100 nm, which is 100 nm. p) depends on the In content and thickness of the QWs, whereas the InGaN-ZnSnGa2N4 (IGN-ZTGN based QW structure offers more flexibility and allows the λ p This allows for a wider range of adjustments.

[0108] A self-consistent six-band k·p method was used to obtain the band structures of the proposed IGN-ZTGN QWs as well as conventional QWs. A 6×6 diagonalized k·p Hamiltonian was used to determine the hole energy bands. A parabolic band structure was assumed for the electrons in the conduction band. The effects of strain, spontaneous and piezoelectric polarization, carrier screening, and valence band mixing were considered. The spontaneous polarization of ZnSnGa2N4 was also considered. As the structures are proposed for LED applications, the radiative recombination properties are estimated using a 1-5×10 18 cm -3 The study was carried out at a carrier density of .

[0109] To calculate the band structure, the Poisson equation was solved iteratively until convergence was achieved. The confined energy levels and wave functions were obtained by self-consistently solving the Schrödinger and Poisson equations. The spatial overlap between the normalized envelope functions was calculated to obtain the overlap between the electron and hole wave functions. Both TE and TM polarizations were considered in the calculation of the spontaneous emission rate. A detailed description of the numerical formalism is provided elsewhere (Zhao et al. IEEE J. Quantum Electron. 2009, 45, 66). Table 2 summarizes the parameter values ​​used in the simulations, using the same notation used elsewhere (Zhao et al. IEEE J. Quantum Electron. 2009, 45, 66). [Table 2]

[0110] In Table 2, the band offset values ​​of ZnSnGa2N4 with GaN were obtained based on experimental results (Zhang et al. Cryst. Growth Des. 2022, 22, 5004), while other parameters were determined by taking the linear dependence of the alloy composition based on the values ​​of ZnSnN2 and GaN (Punya et al. Phys. Rev. B 2013, 88, 075302; Jaroenjittichai et al. Phys. Rev. B 2017, 96, 079907; III-Nitride Semiconductors and Their Modern Devices, Oxford University Press, Oxford, New York, 2013; Park et al. Phys. Rev. B 1999, 59, 4725; Punya et al. Phys. Status Solidi C 2011, 8, 2492).

[0111] Band diagram and spontaneous emission characteristics. 0.25 Ga 0.75 N(IGN)QW and 2nm In 0.2 Ga 0.8 N-0.6nm ZnSnGa2N4-2nm In 0.2 Ga 0.8 N-1.5nm Al 0.2 Ga 0.8 The conduction and valence band structures of the N(IGN-ZTGN) QWs are plotted in Figures 21A and 21B, respectively. Both structures were designed to have a peak emission wavelength of about 590 nm. The corresponding electronic wavefunctions (ψ) for the first confined conduction energy state are e1 ) and the hole wave function (ψ hh1 ) is also plotted. As shown in FIG. 21A, the IGN QW exhibits severe band bending, and the electron and hole wavefunctions are spatially separated. As a result, the electron-hole wavefunction overlap Γ e1-hh1is calculated to be only 5%. However, the IGN-ZTGN QW shown in FIG. 21B has strong hole wavefunction confinement and enhanced electron-hole wavefunction overlap of 18%. Notably, the In composition in the InGaN layer of the IGN-ZTGN QW is 20%, which is lower than that of the conventional IGN QW (25%). As a result, it is expected that this structure will eventually reduce the efficiency drop caused by high In content at longer emission wavelengths.

[0112] The spontaneous emission spectra of the IGN-ZTGN QWs were measured using a range of 1–5×10 18 cm -3 were calculated for carrier concentrations of 1 × 10 and compared with conventional IGN QWs. As shown in Figure 22A, both QW structures have carrier concentrations of 1 × 10 18 cm -3 The peak spontaneous emission intensity (I p ) is 1 × 10 18 cm -3 From 5×10 18 cm -3 With increasing carrier concentration to 5.0×10 26 s -1 cm -3 eV -1 to 1.2 × 10 28 s -1 cm -3 eV -1 while the I of the IGN-ZTGN QW increases to p is 2.0 x 10 25 s -1 cm -3 eV -1 From 5.9 × 10 26 s -1 cm -3 eV -1 to , which corresponds to an improvement of about 17 to 25 times. According to Fermi's golden rule, the improved I p is attributed to the increased overlap of electron-hole wavefunctions in the IGN-ZTGN QW active region.

[0113] R is the spontaneous radiative recombination rate per unit volumesp is calculated by integrating the spontaneous emission spectrum over the entire wavelength range. As shown in FIG. 22B, R sp increases monotonically with increasing carrier concentration for both QW structures. The IGN-ZTGN QWs have about 14 times the R sp Quantitatively, the R sp is 1-5×10 18 cm -3 For a carrier concentration of 5.0×10 26 s -1 cm -3 to 1.2 × 10 28 s -1 cm -3 while IGN QW's R sp is 2.7 x 10 25 s -1 cm -3 From 8.5×10 26 s -1 cm -3 It should be noted that the IQE of an LED is determined by the ratio of the radiative recombination rate to the total recombination rate (including both radiative and non-radiative components). In this case, considering the lower non-radiative recombination expected in IGN-ZTGN QWs due to the lower In content of InGaN grown at relatively high temperatures, an even better performance in IQE can be expected for the QW design described herein. Furthermore, this structure should be ready for MOCVD epitaxy based on the recently established pulsed mode growth of stoichiometric ZnSnGa2N4 films on GaN (Zhang et al. Cryst. Growth Des. 2022, 22, 5004).

[0114] Conclusion. In conclusion, the simulation of QW design of amber LED using InGaN-ZnSnGa2N4 QW active layer is studied. Experimentally measured band offset between ZnSnGa2N4 and GaN is used in the simulation. Due to the large valence band offset, strong confinement of hole wavefunction is achieved by inserting a thin layer of ZnSnGa2N4 into InGaN QW. As a result, the peak spontaneous emission intensity and spontaneous luminescence radiative recombination velocity of InGaN-ZnSnGa2N4 QW show about 17-25 times and 14 times enhancement compared to conventional InGaN QW. In addition, to benefit from the smaller band gap of ZnSnGa2N4 and the larger valence band offset by GaN, the In content of InGaN layer needs to be lower to obtain amber emission around 590 nm. The proposed InGaN-ZnSnGa2N4 QW structure shows great potential to address the challenge of improving the efficiency of InGaN QW-based LEDs emitting beyond green. Based on this design, it is promising to develop high performance III-nitride based LEDs emitting throughout the visible wavelength regime.

[0115] Other advantages which are obvious and inherent to the present invention will be apparent to those skilled in the art. It will be understood that certain features and subcombinations are useful and may be employed without reference to other features and subcombinations. This is contemplated by and within the scope of the claims. Since many possible embodiments can be made of the present invention without departing from its scope, it is to be understood that all matters herein described or shown in the accompanying drawings should be interpreted as illustrative and not in a limiting sense.

[0116] The methods of the appended claims are not limited in scope by the specific methods described herein, which are intended as illustrations of some aspects of the claims, and any methods that are functionally equivalent are intended to fall within the scope of the claims. Various modifications of the methods in addition to those shown and described herein are intended to fall within the scope of the appended claims. Furthermore, only certain representative method steps disclosed herein are specifically described, but other combinations of method steps are also intended to fall within the scope of the appended claims even if not specifically recited. Thus, although combinations of steps, elements, components, or ingredients may be explicitly described herein or less, other combinations of steps, elements, components, and ingredients are included even if not explicitly described.

Claims

1. 1. A photonic material comprising: In y G 1-y a first layer comprising N, wherein y is 0 to 0.8; (Zn a Sn b Ge c ) x G d N 2 A second layer comprising: x is greater than 0 and less than 1; a, b, c, and d are each independently 0 to 1; with the proviso that at least one of a, b, or c is greater than 0; and In z G 1-z a third layer comprising N, wherein z is 0 to 0.8; a second layer disposed between and in contact with the first layer and the third layer such that the second layer is sandwiched between the first layer and the third layer;

2. 2. The photonic material of claim 1, wherein y and / or z is between 0.1 and 0.5, between 0.1 and 0.3, or y and / or z is 0.

2.

3. The photonic material of claim 1 or 2, wherein the first layer has a first average thickness of 0.1 nm to 5 nm.

4. The photonic material of any one of claims 1 to 3, wherein the first layer has a first average thickness of from 1 nm to 3 nm.

5. The photonic material of any one of claims 1 to 4, wherein the second layer has a second average thickness of 0.1 nm to 5 nm.

6. The photonic material of any one of claims 1 to 5, wherein the second layer has a second average thickness of 0.5 nm to 0.7 nm.

7. The second layer is (ZnSn) 0.5 GaN 2 The photonic material according to any one of claims 1 to 6, comprising:

8. d is equal to 1-x, so that the second layer is a Sn b Ge c ) x G 1-x N 2 The photonic material of any one of claims 1 to 7, comprising:

9. The second layer is (ZnSn) 0.5 G 0.5 N 2 9. The phonic material of claim 1, comprising:

10. The photonic material of any one of claims 1 to 9, wherein the third layer has an average third thickness of 0.1 nm to 5 nm.

11. The photonic material of any one of claims 1 to 10, wherein the third layer has a third average thickness of 1 to 3 nm.

12. 12. The photonic material of any one of claims 1 to 11, wherein the photonic material has an average composite thickness of 0.5 nm to 10 nm, the average composite thickness being the sum of the first average thickness, the second average thickness, and the third average thickness.

13. 13. The photonic material of claim 12, wherein the average composite thickness is between 1 nm and 5 nm, between 2.5 nm and 5 nm, or between 4 nm and 5 nm.

14. The third layer further includes a fourth layer disposed on the third layer such that the fourth layer is sandwiched between the second layer and the fourth layer, the fourth layer being composed of Al. w G 1-w 14. The photonic material of claim 1, comprising N and w is 0 to 1.

15. 15. The photonic material of claim 14, wherein w is between 0.1 and 0.5 or between 0.1 and 0.

3.

16. 16. The photonic material of claim 14 or 15, wherein w is 0.

2.

17. The photonic material of any one of claims 14 to 16, wherein the fourth layer has a fourth average thickness of 0.5 nm to 5 nm.

18. The photonic material of any one of claims 14 to 17, wherein the fourth layer has a fourth average thickness of from 0.5 nm to 4 nm, from 1 nm to 2 nm, or from 1.4 nm to 1.6 nm.

19. 19. The photonic material of any one of claims 14 to 18, further comprising a fifth layer disposed on the fourth layer such that the fourth layer is sandwiched between the fifth layer and the third layer, the fifth layer comprising GaN.

20. 20. The photonic material of claim 19, wherein the fifth layer has a fifth average thickness of 1 nm to 15 nm.

21. 21. The photonic material of any one of claims 1 to 20, further comprising a sixth layer disposed on the first layer such that the first layer is sandwiched between the sixth layer and the second layer, the sixth layer comprising GaN.

22. 22. The photonic material of claim 21, wherein the sixth layer has a sixth average thickness of 1 nm to 15 nm.

23. 23. The photonic material of any one of claims 1 to 22, wherein the photonic material has an electron wavefunction having a first confined state and a hole wavefunction having a first confined state, and an overlap of the electron wavefunction and the hole wavefunction at the first confined state in the photonic material is 1% or more, 5% or more, 15% or more, or 20% or more.

24. 24. The photonic material of any one of claims 1 to 23, wherein the photonic material has a spontaneous emission spectrum with a peak wavelength of 500 nm or more, 550 nm or more, 600 nm or more, 650 nm or more, 700 nm or more, 1000 nm or more, or 1200 nm or more.

25. 25. The photonic material of any one of claims 1 to 24, wherein the photonic material has a spontaneous emission spectrum with a peak wavelength between 580 nm and 600 nm.

26. The photonic material of any one of claims 1 to 25, wherein the photonic material exhibits strong hole confinement in the second layer.

27. The photonic material is 1×10 18 cm -3 ~5×10 18 cm -3 With a carrier concentration of 1×10 25 s -1 cm -3 27. The photonic material of any one of claims 1 to 26, having a spontaneous radiative recombination rate per unit volume of at least 100 nm.

28. The spontaneous emission spectrum of the photonic material exhibits a peak wavelength greater than or equal to 500 nm, and the peak wavelength is greater than or equal to 1×10 18 cm -3 ~5×10 18 cm -3 With a carrier concentration of 1×10 25 s -1 cm -3 eV -1 The photonic material according to any one of claims 1 to 27, having a strength equal to or greater than 100%.

29. The photonic material of any one of claims 1 to 28, wherein the photonic material comprises a quantum well structure.

30. A light emitting diode (LED) comprising a quantum well structure comprising the photonic material of any one of claims 1 to 29.

31. 30. A method of use of the photonic material according to any one of claims 1 to 29, comprising using the photonic material in a semiconductor laser, a photovoltaic device, a solar cell, a photodetector or the like.

32. A method for producing a photonic material according to any one of claims 1 to 29, wherein the method comprises MOCVD.

33. 33. The method of claim 32, wherein the method comprises pulsed MOCVD.

Citation Information

Patent Citations

  • Photonic materials

    US20200295226A1